Wall, John (2022). Give Children the Vote. On Democratizing Democracy. Bloomsbury Academic, 246 pp. ISBN: HB: 978-1-3501-9628-5. - Gaitán, Lourdes (Sociedad e Infancias, 2024)
This book reflects the author's conviction that all age limits on the right to vote must be eliminated. A conviction based on his own observation, over the years, of the different expressions of political action developed by boys and girls, from a very early age, throughout the world. The book under discussion consists of seven chapters and concludes with a “manifesto for children’s suffrage” in which the author summarizes his requests to current democracies for this purpose.